(untitled) (Revista de Ciências Agroveterinárias, 2023)
The purpose of this note is to characterize the degree of inclusion of Agroecology in the curricula of undergraduate courses in Zootechnics offered in public institutions of higher education in Brazil, thus assessing the presence as well as the absence of disciplines in their curricular matrices. Of the 74 Brazilian institutions that offer undergraduate courses in Zootechnics, only 24 have Agroecology in their curricula. The offer of Agroecology and related disciplines is present in 16 states, in all regions of the country.